Bioprocess optimization of PHB homopolymer and copolymer P3 (HB-co-HV) by Acinetobacter junii BP25 utilizing rice mill effluent as sustainable substrate. Issue 11 (3rd June 2018) - Sabapathy, Poorna Chandrika; Devaraj, Sabarinathan; Parthiban, Anburajan; Kathirvel, Preethi
ABSTRACT: The potential use of parboiled rice mill effluent as a cheap substrate for the production of homopolymer and copolymer of Polyhydroxyalkanoates (PHAs) by Acinetobacter junii BP 25 was investigated for the first time. Process optimization by one factor at a time led to homopolymer polyhydroxybutyrate (PHB) production of 2.64 ± 0.18 g/l with 94.28% PHB content using a two-stage batch cultivation mode. BP 25 furthermore produced polyhydroxybutyrate-co-hydroxyvalerate (P3 (HB-co-HV)), with the addition of valeric acid as an additive to the substrate, yielding (2.56 ± 0.12 g/l dry biomass, 2.20 ± 0.15 g/l PHA) a copolymer content of 85.93%. Thus, rice mill effluent can be an effective and relatively low-cost alternative for the production of PHA, replacing the pure substrates. GRAPHICAL ABSTRACT: